Study of defects in implanted silica glass by depth profiling Positron Annihilation Spectroscopy - Brusa, R. S. (2010)
Positron Annihilation Spectroscopy (PAS) performed with continuous and pulsed positron beams allows to characterize the size of the intrinsic nano-voids in silica glass, their in depth modification after ion implantation and their decoration by implanted ions. Three complementary PAS techniques, lifetime spectroscopy (LS), Doppler broadening spectroscopy (DBS) and coincidence Doppler broadening spectroscopy (CDBS) will be illustrated by presenting, as a case study, measurements obtained on virgin and gold implanted silica glass.